Tinjauan Penologi Dan Panitensier Terhadap Perlindungan Hukum Bagi Anak Sebagai Korban Bullying Di Lingkungan Pendidikan - Aprianti Lubis; Noval Dwi Satria; Faris Meode Togatorop; Anjar Rusadi; Edo Panangian Simbolon (CV. ITTC INDONESIA, 2025)
Bullying against children is a serious issue that requires proper legal handling. The main purpose of writing this research is to evaluate the effectiveness of legal protection for children as victims of bullying in Indonesia. The legal issue raised is how the law in Indonesia protects children from bullying and whether the protection is effective enough or not. The methodology used in this study is to use This research is normative legal research or library legal research, in accordance with Peter Mahmud Marzuki's view that legal research always has a normative nature. The results of the study indicate that, although there are laws that protect children from bullying, their implementation is still less than optimal. Contributing factors include a lack of understanding of the law and children's rights, as well as a lack of strict sanctions for perpetrators of bullying. This study shows the need for stricter law enforcement to protect children from bullying and based on the law that is aspired to in Indonesia.